2008
DOI: 10.1007/s11738-008-0150-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth regulators, temperature and sucrose on shoot proliferation from the stem disc of Chinese jiaotou (Allium chinense) and in vitro bulblet formation

Abstract: In vitro shoot proliferation from stem disc of Allium chinense, a vegetatively propagated plant, was investigated in this experiment. In the present study, shoots were formed directly on stem discs on a medium containing 1 mg/l N 6 -benzyladenine (BA) and 0.5 mg/lanaphthaleneacetic acid (NAA). These shoots were further cultured on MS media supplemented with various levels of BA in combination with NAA, and new shoot clusters developed easily from the explants cultured despite considerable differences in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 33 publications
1
14
0
4
Order By: Relevance
“…This was shown by Su et al (2011) who found that a low concentration of auxin combined with cytokinin might aid in shoot initiation. Hence, the ratio of cytokinin to auxin is a critical determinant of organogenesis in plant tissue culture (Xu et al, 2008). Aggarwal et al (2010) found that the combination of auxin and cytokinin is effective in inducing shoot from the leaf explant of Eucalyptus tereticornis.…”
Section: Shoot Induction From In Vitro Stem Explantsmentioning
confidence: 99%
“…This was shown by Su et al (2011) who found that a low concentration of auxin combined with cytokinin might aid in shoot initiation. Hence, the ratio of cytokinin to auxin is a critical determinant of organogenesis in plant tissue culture (Xu et al, 2008). Aggarwal et al (2010) found that the combination of auxin and cytokinin is effective in inducing shoot from the leaf explant of Eucalyptus tereticornis.…”
Section: Shoot Induction From In Vitro Stem Explantsmentioning
confidence: 99%
“…Therefore, MS medium was the most effective for growth in I. odaesanensis. BA plays a key role in shoot regeneration in vitro (Ayabe et al 1995;Ayabe et al 1998;Guo et al 2005;Xu et al 2008). In the present experiment, BA enabled shoot regeneration at a frequency of up to 100% when rhizome explants were cultured on medium with 1.0 or 3.0 mg/l BA, although BA at a level of 3.0 mg/l showed a suppressive effect on shoot differentiation (Table 2).…”
Section: Resultsmentioning
confidence: 50%
“…1F). BA plays a key role in shoot regeneration in vitro (Ayabe et al 1995;Ayabe and Sumi 1998;Guo et al 2005;Xu et al 2008). In the present experiment, BA induced shoot regeneration at the rate of 100% when cultured on medium with 1.0 or 3.0 mg・L -1 BA, although the highest BA concentration at 3.0 mg・L -1 appeared to show a suppressive effect on shoot differentiation (Table 2).…”
Section: Plantlet Production and Soil Transfermentioning
confidence: 48%